Effects of cubicle characteristics on animal welfare indicators in dairy cattle. (8th September 2020) - Gieseke, D.; Lambertz, C.; Gauly, M.
Abstract : Cubicle characteristics such as cubicle dimensions or management factors such as cow-to-cubicle ratio could affect health and behaviour of dairy cows. The objective of this study was to estimate effects of cubicle characteristics on animal welfare indicators in dairy cattle. A total of 64 loose housing farms in Germany were assessed once during the winter housing period by one experienced assessor. Nearly 15% of the dairy cows had access to pasture during summer months for <6 h/day, whereas 85% were zero-grazing farms. Selected animal welfare indicators (duration of the lying down process, collisions of cows with cubicles, cows lying outside cubicles, cow cleanliness, integument alterations, lameness and subclinical mastitis incidence) of the Welfare Quality® protocol and cubicle characteristics such as cow-to-cubicle ratio and cubicle dimensions were recorded. Data were statistically analysed using a multiple linear regression approach. Pasture access and cubicle type were considered as potential influencing factors. Wider cubicles positively affected the proportion of dairy cows with dirty flanks (−18.5% per 10 cm increase) but increased the number of cows with severe integument alterations (+8.9% per 10 cm increase). Larger lying areas reduced the percentage of cows with dirty udders (−2.9% per 10 cm 2 increase). Longer distances from neck rail to curb were associated with higher prevalence of cows with dirty flanks (+3.1% per 10 cm increase) and subclinical mastitis incidence (+1.2% per 10 cm increase). With increasing neck rail height, the duration of the lying down process (−0.1 s per 10% increase), the percentages of cows with dirty legs (−8.4% per 10 cm increase), dirty udders (−7.0% per 10 cm increase) and severe lameness (−3.0% per 10 cm increase) decreased. Compared with rubber mat-equipped cubicles, deep-bedded cubicles showed a reduction in the lying down duration (−0.8 s), percentages of cows with dirty legs (−34.2%), dirty udders (−30.5%) and lesions and swellings (−13.1%). Compared with farms that did not provide any summer grazing, pasture access was associated with an increase of cows with severe lameness (+5.6%). Contrastingly, the number of cows with subclinical mastitis incidence was lower when cows had access to pasture in summer (−5.4%). Findings of the present study indicate several associations between cubicle characteristics and animal welfare in dairy cattle. Bedding type was found as the most influencing factor in terms of health and behaviour. Results of this study are valuable for farmers to identify the optimal cubicle design and improve the animal welfare level.